Analysis Of Population Administration Services Government Apparatus In Kalibunder District Office Sukabumi Regency - Dede Riansyah (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The sub-district is one of the spearheads in providing a service, because the sub-district is one of the institutions that are close to the community, especially in rural areas. One of the services that is often carried out by the community in the area is services related to population administration. Population administration services carried out in Kalibunder District are one of the structuring efforts in controlling population documents. The extent of population administration services, the authors limit to three services, namely: Identity Card Services (e-KTP), Family Card Services (KK), Birth Certificates. The tasks carried out by the apparatus or sub-district employees where the apparatus services carried out by the Kalibunder sub-district employees are deemed not optimal, ranging from service time, service costs, to equal rights in receiving services. The theory used by the author to measure the service parameters at the Kalibunder sub-district office, Sukabumi Regency uses the Sinambela theory, namely: transparency, accountability, conditional, participatory, equal rights and balance of rights and obligations. And the author uses qualitative research methods